PENGARUH PROFITABILITAS, LIKUIDITAS, DAN LEVERAGE TERHADAP HARGA SAHAM DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI TAHUN 2018-2022 - Fiqih Dwi Lestari; Rika Rahayu (Jurnal Ekonomi Dan Bisnis, 2024)
Changes in share prices show positive sentiment towards the global economy, improvement in the domestic economy, and continued improvement in company performance. Therefore, stock price changes should be taken into consideration. This research aimed to examine the effect of profitability ratio, liquidity, and leverage on the stock price with the firm size as a moderating variable at the Food and Beverages companies listed on the Indonesia Stock Exchange (IDX). The profitability used return on asset, return on equity, net profit margin, earning per share, quick ratio, and cash ratio. Moreover, the liquidity had a current ratio. Then, leverage used debt to asset ratio, debt to equity ratio, long term debt to equity ratio, and time interest earned. Furthermore, the research was quantitative. There were 160 data samples of Food and Beverage companies listed on the Indonesia Stock Exchange (IDX). Additionally, the data analysis technique used Partial Least Square (PLS). The result showed that profitability affected the stock price. However, both liquidity and leverage did not affect the stock price. In addition, firm size was able to moderate the effect of profitability on stock price. In contrast, firm size was not able to moderate the effect of liquidity on stock price. On the other hand, firm size was able to moderate the effect of leverage on stock price.